Ferroelectricity and Rashba effect in a two-dimensional Dion-Jacobson hybrid organic-inorganic perovskite - Park, In-Hyeok (2020)
Hybrid organic-inorganic perovskites (HOIPs) are a new generation of high-performance materials for solar cells and light emitting diodes. Beyond these applications, ferroelectricity and spin-related properties of HOIPs are increasingly attracting interests. The presence of strong spin-orbit coupling, allied with symmetry breaking ensured by remanent polarization, should give rise to Rashba-type splitting of electronic bands in HOIP. However, the report of both ferroelectricity and Rashba effect in HOIP is rare. Here we report the observation of robust ferroelectricity and Rashba effect in two-dimensional Dion-Jacobson perovskites.